Change in exercise capacity, physical activity and motivation for physical activity at 12 months after a cardiac rehabilitation program in coronary heart disease patients: a prospective, monocentric and observational study - Da Ros Vettoretto, Paul; Bouffart, Anne-Armelle; Gourronc, Youna; Baron, Anne-Charlotte; Gaume, Marie; Congnard, Florian; Noury-Desvaux, Bénédicte; de Müllenheim, Pierre-Yves (PeerJ, 2025)
Background Exercise capacity (EC) and physical activity (PA) are relevant predictors of mortality in patients with coronary heart disease (CHD) but the CHD-specific long-term trajectories of these outcomes after a cardiac rehabilitation (CR) program are not well known. The main objective of this study was to determine the mean change in EC (6-min walking test (6MWT) distance) in CHD patients at 12 months after a CR program compared to the end of the program. We also performed a series of exploratory analyses: (i) estimating the decile shifts and the typical (median) individual change for EC, PA (International Physical Activity Questionnaire-Short Form Metabolic Equivalent of Task (IPAQ-SF MET)-min/week), and motivation for PA (Echelle de Motivation envers l’Activité Physique en contexte de Santé (EMAPS) scores) over the 12-month follow-up period; (ii) characterizing the PA motivational profiles at the end of the program and 12 months after the program; (iii) characterizing the barriers to PA perceived at 12 months; and (iv) estimating the categories of changes in EC and PA over time and their potential predictors. Methods Eighty-three patients were recruited at the end of a CR program. Results For an average patient, EC was trivially increased at 12 months. However, the decile shifts analysis did not confirm that the positive shift of the distribution of the performances over time was uniform. In contrast, we observed a significant decrease in PA between the end of the program and 12 months post-program but not between 6 and 12 months post-program when considering both the group of patients as a whole and the typical individual change. The results regarding motivation for PA were mixed, with significant and non-uniform shifts of the deciles towards scores depicting degrees of autonomous and controlled motivations as well as amotivation that would be more in favor of PA, but with no significant typical individual changes except for introjected regulation. Two motivational profiles were identified both at the end of the program and 12 months after the program: one with a very high level of autonomous motivation and a high level of introjected regulation; and another one with a high level of autonomous motivation and a moderate level of introjected regulation. Unfavorable weather, lack of time, fatigue, and fear of injury were the main barriers to PA at 12 months post-program. The change in EC and PA could be categorized into different classes without the possibility to determine any potential predictor of the assignment to a given class. Overall, these results suggest that clinicians managing a CR program with CHD patients as the one implemented in the present study may expect slightly positive or at least steady trajectories in EC, PA (after 6 months), and motivation for PA during the year after the program when considering the bulks of the distributions of patient scores. However, these global trajectories are actually the results of heterogeneous individual changes with some profiles of patients who could need a particular attention.
Keywords: Coronary artery disease; Cardiac rehabilitation program; Walking capacity; Movement behaviours; Self-determined motivation; Follow-up